2017
DOI: 10.1038/ncomms14283
|View full text |Cite
|
Sign up to set email alerts
|

Advanced rechargeable aluminium ion battery with a high-quality natural graphite cathode

Abstract: Recently, interest in aluminium ion batteries with aluminium anodes, graphite cathodes and ionic liquid electrolytes has increased; however, much remains to be done to increase the cathode capacity and to understand details of the anion–graphite intercalation mechanism. Here, an aluminium ion battery cell made using pristine natural graphite flakes achieves a specific capacity of ∼110 mAh g−1 with Coulombic efficiency ∼98%, at a current density of 99 mA g−1 (0.9 C) with clear discharge voltage plateaus (2.25–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
290
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(302 citation statements)
references
References 26 publications
12
290
0
Order By: Relevance
“…The capacity calculated for each tube is listed in Ta ble 1. [68] The storage capacities obtainedf or the reported SWNTsa re higher than that of the earlier studied graphite cathode( 70 mA hg À1 ), [27][28][29] whichs uggests the application of SWNTsa ss uperior cathode host for Al batteries. For the (10,10) SWNT,t he calculated capacity is 223 mA hg À1 ,w hich furtheri ncreases to 236 to 251 mA hg À1 for the (15,15) and (20,20) SWNT,r espectively,a nd as pecific capacity as high as 275 mA hg À1 can be obtained with the (25,25) SWNT.T he systematici ncrease in capacity as the tube diameter increases is in accord with earlier studies on Li-ion batteries with SWNT electrodes.…”
Section: Open-circuit Voltage and Storage Capacitymentioning
confidence: 66%
See 1 more Smart Citation
“…The capacity calculated for each tube is listed in Ta ble 1. [68] The storage capacities obtainedf or the reported SWNTsa re higher than that of the earlier studied graphite cathode( 70 mA hg À1 ), [27][28][29] whichs uggests the application of SWNTsa ss uperior cathode host for Al batteries. For the (10,10) SWNT,t he calculated capacity is 223 mA hg À1 ,w hich furtheri ncreases to 236 to 251 mA hg À1 for the (15,15) and (20,20) SWNT,r espectively,a nd as pecific capacity as high as 275 mA hg À1 can be obtained with the (25,25) SWNT.T he systematici ncrease in capacity as the tube diameter increases is in accord with earlier studies on Li-ion batteries with SWNT electrodes.…”
Section: Open-circuit Voltage and Storage Capacitymentioning
confidence: 66%
“…[17,18,[20][21][22][23]26] An Al battery that is comprised of three-dimensional graphitic-foamc athode graphite has attracted globala ttention owing to its ultrafast charging rate and the involvement of intercalation/deintercalation of AlCl 4 anions during charging/discharging, respectively. [29][30][31][32] However,m any experimental studies on anion intercalation and the theoretical study we conducted on graphite electrodeh ave shown that the very first intercalation step (cycle) differs from the other successive steps because it involves the activation of partially closed interlayer spaceso f graphite layers during the initial intercalation of the anion, which results in lower discharge capacities. [29][30][31][32] However,m any experimental studies on anion intercalation and the theoretical study we conducted on graphite electrodeh ave shown that the very first intercalation step (cycle) differs from the other successive steps because it involves the activation of partially closed interlayer spaceso f graphite layers during the initial intercalation of the anion, which results in lower discharge capacities.…”
Section: Introductionmentioning
confidence: 96%
“…Thes plitting and merging of the G-band of graphene in the Raman spectra confirm reversible AlCl 4 À1 anion intercalation and deintercalation in graphene layers during charging and discharging, respectively ( Figure 2g). [44] Chen et al again utilized the same high temperature processing technique to obtain defect-free graphene in powder form. It is realized that defects are not only inactive sites but also act as obstacles for AlCl 4 À1 anion percolation.…”
Section: Methodsmentioning
confidence: 99%
“…It resulted in very stable and higher discharge capacity of 123 mAh g À1 over 10 4 cycles at current rate of 5Ag À1 with Coulombic efficiencyo fg reater than 98 % ( Figure 2b). [44] Although natural graphite can reversibly host AlCl 4 À1 anions,i ts hows poor rate capability than fewlayer graphene.Aspecific capacity of only 60 mAh g À1 could be attained at comparatively low current rate of 0.66 Ag À1 .It is shown to be true for pyrolytic graphite as well, which exhibits ac apacity of only 20 mAh g À1 at ac urrent rate of 0.264 Ag À1 . Zhang et al clearly demonstrated enhanced kinetics of AlCl 4 À1 anions in graphene cathodes with reduced crystallite size along c-axis.…”
Section: Electrochemical Performances Of Al-graphene Cellsmentioning
confidence: 99%
“…This communication reports on the construction and testing of a fully functional aqueous Al-ion cell. It should be noted that the majority of Al-ion research focusses on room temperature ionic liquid electrolyte systems (RTILs) theoretically allowing the utilisation of aluminium metals high capacity through reversible deposition [3][4][5][6][7][8][9][10]. The primary research aim becomes the identification of positive electrode materials that will not severely limit cell capacity.…”
Section: Introductionmentioning
confidence: 99%